Α-Synuclein modulates fibronectin expression in the trabecular meshwork independent of TGFβ2. (January 2023) - Adulla, Anika; Patel, Urvi; Ashok, Ajay; Katiyar, Priya; Kaulakis, Mare; Kritikos, Alexander E.; Pillai, Sachin; Lee, HyunPin; Lindner, Ewald; Rhee, Douglas J.; Singh, Neena
Abstract: α-Synuclein (α-Syn) is implicated in Parkinson's disease (PD), a neuromotor disorder with prominent visual symptoms. The underlying cause of motor dysfunction has been studied extensively, and is attributed to the death of dopaminergic neurons mediated in part by intracellular aggregation of α-Syn. The cause of visual symptoms, however, is less clear. Neuroretinal degeneration due to the presence of aggregated α-Syn has been reported, but the evidence is controversial. Other symptoms including those arising from primary open angle glaucoma (POAG) are believed to be the side-effects of medications prescribed for PD. Here, we explored the alternative hypothesis that dysfunction of α-Syn in the anterior eye alters the interaction between the actin cytoskeleton of trabecular meshwork (TM) cells with the extracellular matrix (ECM), impairing their ability to respond to physiological changes in intraocular pressure (IOP). A similar dysfunction in neurons is responsible for impaired neuritogenesis, a characteristic feature of PD. Using cadaveric human and bovine TM tissue and primary human TM cells as models, we report two main observations: 1) α-Syn is expressed in human and bovine TM cells, and significant amounts of monomeric and oligomeric α-Syn are present in the AH, and 2) primary human TM cells and human and bovine TM tissue endocytose extracellular recombinant monomeric and oligomeric α-Syn via the prion protein (PrP C ), and upregulate fibronectin (FN) and α-smooth muscle actin (α-SMA), fibrogenic proteins implicated in POAG. Transforming growth factor β2 (TGFβ2), a fibrogenic cytokine implicated in ∼50% cases of POAG, is also increased, and so is RhoA-associated coiled-coil-containing protein kinase 1 (ROCK-1). However, silencing of α-Syn in primary human TM cells reduces FN, α-SMA, and ROCK-1 in the absence or presence of over-expressed active TGFβ2, suggesting modulation of FN and ROCK-1 independent of, or upstream of TGFβ2. These observations suggest that extracellular α-Syn modulates ECM proteins in the TM independently or via PrP C by activating the RhoA-ROCK pathway. These observations reveal a novel function of α-Syn in the anterior eye, and offer new therapeutic options. Highlights: α-Synuclein (α-Syn) is expressed by trabecular meshwork (TM) cells. Soluble monomeric and oligomeric α-Syn is present in the aqueous humor (AH). Uptake of extracellular α-Syn by TM cells increases fibronectin (FN) and ROCK-1. α-Syn is internalized by the prion protein (PrP C ), causing its downregulation. α-Syn modulates ECM proteins directly, via PrP C, or through alternative pathways.